Mediação escolar com alunos autistas: contribuições a partir da psicanálise - Nathália Lopes Machado (2022)
This research aimed at investigating mediation in schools, which took place within the process of school inclusion of autistic students, having lacanian psychoanalysis as theoretical support. By being called out to welcome in regular classrooms children and adolescents that had previously built their educational life in special classes or in specialized institutions before, the schools demanded the presence of a supporting professional, who will be named in this work as school mediator. Their role is to act as an inclusion agent, providing support in activities that involve the educational process, provided that some sort of intervention is needed. The school mediator is able to act with several student’s profiles, however, this investigation focuses on autistic students, taking into account that they are individuals with certain subjective specificities, as it is indicated by Psychoanalysis. The following questions guide the research: What is the school mediator’s main task regarding autistic students? Are there any particularities in their practice with those students? Which interventions does the school mediator carry out in order to deal with issues related to the schooling of autistic individuals? As regards data collection, interviews were conducted, remotely as a result of COVID-19, with seven school mediators that have worked in private and public institutions, with the aim of obtaining reports regarding the practice with assisted autistic students. Through the experiences reported, it was possible to identify the relevance of observing, so that the school mediator may get to know and understand the student, by means of a comprehension of their subjective manifestations, interests, the way they learns and relate with others, so that it becomes possible to elaborate strategies of intervention and accomplish school mediation. The experiences allowed us to identify that the school mediator can act as support, while they aid the student in particular tasks, actions and shared activities with others and, at the same time, be leveled as support, since they can protect the individual from certain situations which are felt as invasive. Hence, the school mediator must be aware of the importance of the swing movement that must be part of their practice, not allowing too much presence, which can provoke the opposite effect to school inclusion, and promoting the necessary space at given moments.